Noise Pollution Monitoring and Noise Mapping at Rajshahi University, Bangladesh - Hasan, Md Alamgir; Kalam Azad, Md Abul; Kamruzzaman, Md; Moniruzzaman, Md (Journal of Engineering Science, 2025)
Noise pollution is harmful to human health. Loud noise generation is a growing issue across the world as well as in Bangladesh. A relatively quiet environment is required in educational areas. So, an acoustic study was conducted for the assessment of noise levels on the campus of Rajshahi University. The noise monitoring was carried out at twenty-one locations, and the traffic count was carried out at six road intersections simultaneously at three specific times (morning, afternoon, and evening) during the peak period from January to February 2023. A calibrated digital sound level meter was used to monitor the noise level, and traffic volume was counted manually. Noise mapping was generated by Kriging interpolation analysis using GIS software. Results show that a maximum noise value Lmax of 110.1 dBA was found around the central library in the evening periods, followed by 105.3 dBA at an entrance gate adjacent to the busy road; however, the Lmax value randomly exceeded 100 dBA at the three entrance points. The equivalent continuous noise level, Leq, was measured between 53 and 77.3 dBA. The highest Leq of 77.3 dBA was found at an entrance point, and a minimum noise level of 46.4 dBA was observed in a residential zone. A significant correlation between traffic volume and noise level shows that the flow of traffic influences the noise level in the campus area. The mapping visualizes the unknown point values based on the weighted average of known point values to form a noise map. These findings are much higher than the acceptable limit for noise levels in sensitive areas like educational institutions in Bangladesh. Whereas limit 35 dBA is advised by WHO for educational institutions. The noise level was found to increase with an increase in motorized traffic volume, where three-wheeled autorickshaws were dominant, followed by two-wheeled motorcycles. Proximity of the national highway and railway on two different sides of the study area. Loudspeakers for various events enhanced the noise level. The collected data were used in GIS software to produce the noise map, and the outcome obtained from it revealed the spatial extent of noise variations throughout the university campus in the form of noise maps. Journal of Engineering Science 16(1), 2025, 61-68